2004
DOI: 10.1637/7137
|View full text |Cite
|
Sign up to set email alerts
|

Typing of Haemophilus paragallinarum Strains by Using Enterobacterial Repetitive Intergenic Consensus-Based Polymerase Chain Reaction

Abstract: The enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR) technique was used for fingerprinting of reference strains and Mexican isolates of Haemophilus paragallinarum. A total of nine ERIC patterns were given by the nine serovar reference strains of this bacteria. Two Modesto (C-2) reference strains from different sources showed the same ERIC pattern. Seventeen ERIC patterns were obtained among 29 Mexican isolates included in the study, belonging to serovars prevalent in Mexico … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
1
13
1
1
Order By: Relevance
“…Enterobacterial repetitive intergenic consensus (ERIC)-PCR of Dutch isolates was performed according to the method of Soriano et al (2004).…”
Section: Methodsmentioning
confidence: 99%
“…Enterobacterial repetitive intergenic consensus (ERIC)-PCR of Dutch isolates was performed according to the method of Soriano et al (2004).…”
Section: Methodsmentioning
confidence: 99%
“…However, the PCR could not identify serovars A, B and C. Soriano et al reported that an enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR) could identify each serovar [13], but it would not be easy to analyze the results, since ERIC-PCR showed many patterns even within each serovar. Therefore, we examined more simplified methods using PCR.…”
mentioning
confidence: 99%
“…The ERIC-PCR was performed as described by Soriano et al (2004c) using primer pair ERIC1R (5 ′ -ATG-TAAGCTCCTGGGGATTCAC-3 ′ ) as reverse primer and ERIC2 (5 ′ -AAGTAAGTGACTGGGGTGAGCG-3 ′ ) as forward primer. All reactions were performed in duplicate using the same PCR kit and thermocycler as described previously.…”
Section: Enterobacterial Repetitive Intergenic Consensus (Eric)-pcrmentioning
confidence: 99%
“…paragallinarum from other species and does not differentiate serovars within the species (Chen et al, 1996). Molecular typing methods have been reported for the differentiation of different serovars and these methods include Enterobacterial Repetitive Intergenic Consensus (ERIC) polymerase chain reaction (PCR) (Soriano et al, 2004c), Multiplex PCR and Restriction Fragment Length Polymorphism -PCR (Sakamoto et al, 2011). In 2014, research suggested that the Multiplex PCR method is flawed when applied to the identification of unknown serovars of Av.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation